Eucommia ulmoides Olive Male Flower Extracts Ameliorate Alzheimer’s Disease-Like Pathology in Zebrafish via Regulating Autophagy, Acetylcholinesterase, and the Dopamine Transporter - Sun, Chen; Zhang, Shanshan; Ba, Shuaikang; Dang, Jiao; Ren, Qingyu; Zhu, Yongqiang; Liu, Kechun; Jin, Meng (Frontiers in Molecular Neuroscience, 2022)
Alzheimer’s disease (AD) is the most prevalent neural disorder. However, the therapeutic agents for AD are limited. Eucommia ulmoides Olive (EUO) is widely used as a traditional Chinese herb to treat various neurodegenerative disorders. Therefore, we investigated whether the extracts of EUO male flower (EUMF) have therapeutic effects against AD. We focused on the flavonoids of EUMF and identified the composition using a targeted HPLC-MS analysis. As a result, 125 flavonoids and flavanols, 32 flavanones, 22 isoflavonoids, 11 chalcones and dihydrochalcones, and 17 anthocyanins were identified. Then, the anti-AD effects of the EUMF were tested by using zebrafish AD model. The behavioral changes were detected by automated video-tracking system. Aβ deposition was assayed by thioflavin S staining. Ache activity and cell apoptosis in zebrafish were tested by, Acetylcholine Assay Kit and TUNEL assay, respectively. The results showed that EUMF significantly rescued the dyskinesia of zebrafish and inhibited Aβ deposition, Ache activity, and occurrence of cell apoptosis in the head of zebrafish induced by AlCl3. We also investigated the mechanism underlying anti-AD effects of EUMF by RT-qPCR and found that EUMF ameliorated AD-like symptoms possibly through inhibiting excessive autophagy and the abnormal expressions of ache and slc6a3 genes. In summary, our findings suggested EUMF can be a therapeutic candidate for AD treatment.